2002
DOI: 10.1136/emj.19.1.19
|View full text |Cite
|
Sign up to set email alerts
|

Short-term effectiveness of ceftriaxone single dose in the initial treatment of acute uncomplicated pyelonephritis in women. A randomised controlled trial

Abstract: Objective: To compare the short-term effectiveness of ceftriaxone single dose followed by cefixime with a standard treatment of acute uncomplicated pyelonephritis in women.Methods: An open, prospective, and randomised trial of women with acute uncomplicated pyelonephritis was performed. Group A were given a daily intravenous dose of 1 g ceftriaxone; group B: ceftriaxone 1 g intravenous single dose followed by oral cefixime. When urine culture was received, both groups completed a 10 day treatment based in sens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 11 publications
1
25
0
2
Order By: Relevance
“…One study [42] used a variety of antimicrobial regimens and therefore was not suitable for further evaluation. Eleven randomised studies [47][48][49][50][51][52][53][54][55][56][57][58] were published thereafter. In some of these studies acute uncomplicated pyelonephritis was treated with the same protocol as complicated UTI/pyelonephritis.…”
Section: Treatment Of Uncomplicated Pyelonephritismentioning
confidence: 99%
“…One study [42] used a variety of antimicrobial regimens and therefore was not suitable for further evaluation. Eleven randomised studies [47][48][49][50][51][52][53][54][55][56][57][58] were published thereafter. In some of these studies acute uncomplicated pyelonephritis was treated with the same protocol as complicated UTI/pyelonephritis.…”
Section: Treatment Of Uncomplicated Pyelonephritismentioning
confidence: 99%
“…Sanchez et al [32] reported similar outcomes using one dose of ceftriaxone versus a 3-day course of ceftriaxone followed by oral -lactam therapy in women with uncomplicated pyelonephritis.…”
Section: ) Cephalosporinmentioning
confidence: 55%
“…In any case, microbiological negativity, a frequently chosen end-point in recent clinical trials, may be at odds with the imaging findings, as large lesions (even with abscess evolution) can coexist with negative urine cultures [22,24,[29][30][31][32][33][34].…”
Section: Discussionmentioning
confidence: 99%